PENGARUH PENYIMPANAN SAMPAI ENAM BULAN MENGGUNAKAN BUBUK DAN TANPA BUBUK LADA TERHADAP MUTU LIMABELAS LOT BENIH KEDELAI (GLYCINE MAX L.) - Kurniati, Ayu; Agustiansyah, Agustiansyah; Nurmiaty, Yayuk; Ermawati, Ermawati (JURNAL AGROTROPIKA, 2020)
This study aims to determine the best seed quality from fifteen lots of soybean seeds that are stored for up to six months using pepper powder and without using pepper powder. The treatment was applied in a Completely Randomized Design (CRD) which was repeated three times. The combination of treatments derived from three varieties, namely Anjasmoro, Gerobogan, and Burangrang combined with 5 SP-36 fertilizer doses, namely 0, 100, 150, 200, and 250 kg / ha. The experiment consisted of two experiments. Experiment 1, the fifteen lots of seeds were stored without pepper powder. Experiment 2, the fifteen lots of seeds were ground with pepper in their storage. Storage at room temperature ranges from 28-30oC in the Seed and Plant Breeding Laboratory, Faculty of Agriculture, University of Lampung in October 2017 to April 2018 The results showed that the combination treatment of Burangrang varieties with SP-36 250 kg / ha fertilizer stored without pepper powder or pepper powder was able to maintain its higher quality compared to other treatment combinations after being stored for up to six months Key words: Fertilizer, pepper powder, soybean, storage, variety